2008
DOI: 10.1017/s1751731108002322
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing heifer survival and fertility on commercial dairy farms

Abstract: The average dairy cow survives only three lactations, reducing the availability of replacement heifers. Prenatal losses occur due to early embryonic mortality (about 40%), later embryo loss (up to 20% in high-yielding herds) or abortion (about 5%). A recent survey of 19 UK herds showed that 7.9% of calves were born dead and 3.4% died within 1 month. During the rearing phase, 6.7% of animals were lost before reaching first service at 15 months due to disease or accident and another 2.3% failed to conceive. Many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
0
14

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(141 citation statements)
references
References 45 publications
6
114
0
14
Order By: Relevance
“…One explanation for these differences might be given by Bielfeldt et al (2006), who found out that the target age at first calving significantly differed between herd management systems. Wathes et al (2008) concluded from a review that the main factor when heifers conceive is the pre-pubertal growth rate, which is under both environmental and genetic effect.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for these differences might be given by Bielfeldt et al (2006), who found out that the target age at first calving significantly differed between herd management systems. Wathes et al (2008) concluded from a review that the main factor when heifers conceive is the pre-pubertal growth rate, which is under both environmental and genetic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The first lactation length was shorter with an AFC of more than 34 months. As suggested by Wathes et al (2008), poorly growing animals required more services to conceive, calved later and subsequently performed badly. Milk production during first lactation was maximised with an AFC between 22 and 26 months.…”
Section: Analysis Of First Lactationmentioning
confidence: 97%
“…Most research pertaining to the genetics of reproductive performance in dairy cattle has focused primarily on lactating cows (Royal et al, 2002; Kadarmideen conceive and 3.3% died or were culled due to infertility between 15 months of age and expected calving age. Of the heifers that failed to conceive at 15 months of age, some were reinseminated later in the year and subsequently calved for the first time older than 30 months of age (Wathes et al, 2008). Although management also affects reproductive performance, some of the results observed by Wathes et al, (2008) were also likely due to genetic effects.…”
Section: Introductionmentioning
confidence: 99%